Evaluation of turmeric-mung bean intercrop productivity through competition functions - Mohamaed ISLAM; Mohammad ALAM; Ayman EL SABAGH; Celaleddin BARUTÇULAR; Disna RATNASEKERA; Ferhat KIZILGEÇI; M. Sohidul ISLAM (Acta Agriculturae Slovenica, 2018)
An intercropping experiment was conducted with varying combinations of turmeric and mung bean to find out the efficacy of productivity and economic return through competition functions. Treatments were evaluated on the basis of several competition functions, such as land equivalent ratio (LER), aggressiveness, competitive ratio (CR), monetary advantage index (MAI) and system productivity index (SPI). Results showed that rhizome yields of turmeric were higher in intercropping system than in mono crop. It indicated that intercropping of mung bean did not affect the rhizome yield of turmeric. However, turmeric (100 %) + 3 row mung bean (100 %) in between turmeric lines intercropping system exhibited maximum yield of both the crops as well as turmeric equivalent yield, LER, competitive indices values, SPI and MAI (Tk. 2,44,734.46 ha-1) compared to the other intercropping combinations and the mono crops. Aggressiveness of intercrop indicated dominance of turmeric over mung bean in all the combinations except turmeric (100 %) + 1 row mung bean (33 %). Competition functions of intercroping suggested beneficial association of turmeric and mung bean crops. The study revealed that mung bean could be introduced as intercrop with turmeric without hampering rhizome yield with higher benefit additionally increasing mung bean production area.